KOMUNIKASI PERSUASIF PT HERBA PENAWAR ALWAHIDA INDONESIA (HPAI) DALAM MEMBANGUN JARINGAN DI KOTA PEKANBARU - Putra, Ade Surya Dwi; ", Rumyeni (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Herba Penawar Alwahida Indonesia (HPAI) Company is one of Multi Level Marketing (MLM) company used Halal Network concept where Pekanbaru City Region is the one of the branch company. This research entitled “Persuasif Communication Of PT Herba Penawar Alwahida Indonesia (HPAI) In Develop The Network At The City Of Pekanbaru”. The purpose of this research is determine the credibility of HPAI communicators, delivered message, persuasive communications channels used, feedback from persuasive communication, and persuasive communication strategies conducted by HPAI Partners in building the network in Pekanbaru City.This research was conducted by using qualitative method. There are 5 people be research subjects/informants consisting of HPAI Partners from various levels of agency ranging from Business City Leaders Pekanbaru City to new partners join HPAI. To validity of data used source of triangulation that is Chairman of the Board of Sharia HPAI. To obtain data in this research used interview technique, observation and documentation.The results show that the credibility of HPAI communicators includes expertise supported by the education and training that are followed during the HPAI partnership as well as trust worthiness given by the community as communicators show a harmony between speech and action. Sending massage include verbal and nonverbal messages by using communication channels in the form of offline media, online, electronic media and direct communication. Feedback from persuasive communication obtained communicator by way of evaluating own activities that have been done (internal) and ask for a response from the communicant (external). Persuasive communication strategies used by HPAI partners include: Psychodynamic strategy that is Preparing communication with da'wah; Sociocultural Persuasion Strategy that is by avoiding the use of the term upline and downline in communicating; The Meaning Contuction is by prioritizing on health education rather than selling products.Keyword: HPAI, persuasive communication, network